Use of proton pump inhibitors and the risk of hepatocellular carcinoma: A systematic review and meta-analysis. Issue 10 (October 2019) - Chang, Tien-En; Huang, Yi-Shin; Perng, Chin-Lin; Huang, Yi-Hsiang; Hou, Ming-Chih
Abstract : Background: Worldwide, proton pump inhibitors (PPIs) are commonly used for the treatment of peptic ulcer and gastro-esophageal reflux disease. Recently, concern has arisen over the potential association between PPIs and hepatocellular carcinoma (HCC). The aim of the current study was to evaluate the influence of PPI use on the risk of HCC, through a systematic review and meta-analysis. Methods: A review of all English-language literature was conducted, using the subject search terms: "hepatocellular carcinoma", "liver cancer", "hepatic tumor", and "proton pump inhibitor" in the major medical databases. A meta-analysis of the qualifying publications was then performed. Results: A total of five studies, which had shown that PPIs were associated with HCC (crude risk ratio [RR] = 2.27, 95% confidence interval [CI]: 1.44-3.57; p < 0.01) when an unadjusted RR were adopted, were eligible for meta-analysis. It was observed that the cumulative dose of PPIs may increase the risk of HCC in a linear model ( p < 0.01). However, when using data that were adjusted by comorbidities and concurrent medications, the association between PPIs and HCC became insignificant (adjusted RR = 1.62, 95% CI: 0.89-2.93; p = 0.11) and this result was consistent in the sensitivity analysis. Conclusion: The current meta-analysis has shown that PPI use does not significantly increase the risk of HCC after adjusting for confounding factors. However, further studies are warranted to verify the association between PPIs and HCC in special populations, such as viral or alcoholic liver diseases.